2017
DOI: 10.1177/1077801217732348
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Views on the Impacts, Challenges, and Barriers in Supporting Older Survivors of Sexual Violence

Abstract: Despite half a century of research on both sexual violence and elder abuse, the intersection between the two remains largely unexplored. Using theoretical lenses of feminist criminology and critical feminist gerontology, this article explores the intersection between age and sexual violence drawing on interviews with 23 practitioners supporting older survivors (aged 60 and over). They reported physical and emotional effects of sexual violence leading to limited lifestyles, disengagement from social networks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 56 publications
0
38
0
1
Order By: Relevance
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 107 papers included in the review, some were relevant to more than one of our three review questions. For review question one, we included 78 publications providing information on how sexual assault services address mental health and substance misuse [20, 24-26, 33-106]; for review question two, we included 6 papers of five trial evaluations [84,89,92,[107][108][109]; and for review question three, we included 34 studies on stakeholders' views [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] and 10 policy documents [20,22,[127][128][129][130][131][132]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We found 34 papers [20,25,34,37,44,53,54,60,62,72,78,82,86,90,93,94,97,[110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] relating to 32 studies, which reported stakeholders' views on how sexual assault services should identify and respond to mental health and substance misuse problems for people following sexual assault. Twenty five were peer-reviewed publications [25,34,44,53,54,60,72,78,82,90,94,[110][111][112][113][114]…”
Section: Q3: Studies On Stakeholders' Viewsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of changes faced the forensic examiners regarding the responsibility of dealing with victims and providing effective measures and preventive setting. The most stressful task is to prove the assault and to undertake correct documentation and collection of evidence [2,3]. A genital injury is a type of trauma that has happened as a result of physical contact.…”
Section: Introductionmentioning
confidence: 99%